Plasma and intracellular ribavirin concentrations are not significantly altered by abacavir in hepatitis C virus-infected patients. (10th February 2016) - Fuchs, Edward J.; Kiser, Jennifer J.; Hendrix, Craig W.; Sulkowski, Mark; Radebaugh, Christine; Bushman, Lane; Ray, Michelle L.; Andrade, Adriana
Abstract: Objectives: The objective of this study was to evaluate the effects of abacavir on intracellular ribavirin triphosphate and plasma ribavirin trough concentrations. Methods: Hepatitis C virus-infected subjects who had been cured or failed prior treatment were randomized to 8 weeks of ribavirin alone ( N  = 14; weight-based dosing) or weight-based ribavirin + abacavir ( N  = 14; 300 mg orally every 12 h). Ribavirin trough concentrations were measured on days 14, 28, 42 and 56; PBMCs for ribavirin triphosphate determination were sampled on days 28 and 56, pre-dose and at 6 and 12 h post-dose. ClinicalTrials.gov: NCT01052701. Results: Twenty-six subjects completed the study (24 males, 17 Caucasians, median age 52 years); 2 were excluded for missed pharmacokinetic visits. Fourteen subjects received ribavirin + abacavir and 12 received ribavirin alone. Mean ± SD plasma ribavirin trough concentrations (μg/mL) on days 14, 28, 42 and 56, respectively, were not significantly different with coadministration of abacavir (1.54 ± 0.60, 1.93 ± 0.54, 2.14 ± 0.73 and 2.54 ± 1.05) compared with ribavirin alone (1.48 ± 0.32, 2.08 ± 0.41, 2.32 ± 0.47 and 2.60 ± 0.62) ( P  > 0.40). Mean ribavirin triphosphate intracellular concentrations (pmol/10 6 cells) on days 28 and 56, respectively, did not differ statistically between abacavir users (11.98 ± 9.86 and 15.87 ± 12.52) and non-users (15.91 ± 15.58 and 15.93 ± 12.69) ( P  > 0.4). Adverse events were mild or moderate, except for three grade 3 occurrences of transaminitis, cholecystitis and low absolute neutrophil count that resolved and were judged not attributable to study medications. Conclusions: Abacavir did not significantly alter ribavirin or ribavirin triphosphate concentrations.